Open-label, randomised, multicentre crossover trial assessing two-layer compression bandaging for chronic venous insufficiency: results of the APRICOT trial. (2nd June 2020) - Jonker, Leon; Todhunter, Jane; Robinson, Lesley; Fisher, Stacey
Abstract : Compression bandaging is the mainstay therapy for chronic venous insufficiency and venous leg ulcers, but patient compliance can be challenging due to associated discomfort. The study discussed here aimed to compare AndoFlex TLC Calamine and Coban2 compression bandaging in relation to patient comfort and pruritus symptomology, with severity of pruritus as the primary outcome. This was a multi-centre, prospective, non-blinded, randomised controlled crossover trial involving 39 randomised patients with chronic venous insufficiency patients. In two periods, the patients wore AndoFlex TLC Calamine or Coban2 for 3 weeks each. No significant differences in validated pruritus outcome measures were observed, including a non-significant treatment effect for the severity of pruritus scale (n=35 trial completers; p-value=0.24, Wilcoxon test). However, after trying both bandages, 21 of the 35 patients (60%) definitely preferred AndoFlex TLC Calamine, whereas 4 patients (11%) definitely preferred Coban2. Thus, AndoFlex TLC Calamine compression bandage therapy was preferred by most patients, although this observation could not be confirmed using validated patient-reported outcome measures for pruritus. Further research is indicated to establish if patient preference translates into favourable clinical outcomes. ISRCTN number: ISRCTN95282887